Personal and Perceived Peer Use of and Attitudes Toward Alcohol Among University and College Students in Seven EU Countries: Project SNIPE - AKVARDAR, YILDIZ (ALCOHOL RES DOCUMENTATION INC CENT ALCOHOL STUD RUTGERS UNIV, 2015)
Objective: The objective of this study was to explore perceptions of peer substance use and related attitudes among European students. Challenging perceptions about peer substance use has become the basis of a form of prevention and intervention known as the social norms approach, which can be delivered using personalized online feedback. This article reports baseline alcohol use and attitudes data for university students across Europe collected as part of the Social Norms Intervention for the prevention of Polydrug usE project (Project SNIPE). Method: Students from universities in Belgium, Denmark, Germany, the Slovak Republic, Spain, Turkey, and the United Kingdom were recruited to take part in an online survey by the use of email invitations, social media, classroom announcements, flyers, and stalls in social areas, such as in cafeterias and bars on campus. A total of 4,482 students agreed to participate. Results: Overall, respondents reported both perceived alcohol use and perceived acceptance of alcohol use among their peers that were higher than their own use or acceptance. Perceived peers' behaviors and attitudes were found to be predictive of personal behaviors and attitudes, with some variation across countries and by sex. Conclusions: The results suggest that students at the participating institutions across selected European countries exhibit overall similar patterns of perceptions as have been found on American college campuses. In conjunction with the finding that the perceived norm is predictive of personal behavior and attitudes, this research provides support to the view that the social norms approach may be a viable method to reduce alcohol consumption among students at European universities.
Keywords: SOCIAL NORMS APPROACH; INJUNCTIVE NORMS; DRINKING NORMS; HEAVY DRINKING; BINGE DRINKING; DRUG-USE; MISPERCEPTIONS; INTERVENTION; PREVENTION; CONSEQUENCES